The electoral benefits of opportunistic election timing - Schleiter, P; Tavits, M (University of Chicago Press, 2016)
This study explores the effect of opportunistic election timing on the incumbent’s electoral performance. While the existing literature on parliamentary dissolution and election timing does not directly address this question, we show that the theoretical implications which derive from it lead to contradictory predictions about the ability of incumbent governments to benefit from strategically timed elections. We advance the theoretical debate by presenting the first cross-national comparative analysis of the electoral effects of opportunistic election timing, drawing on an original dataset of 318 parliamentary elections in 27 East and West European countries. In order to identify the effect of opportunistic election calling on incumbent’s electoral performance, we rely on instrumental variable regression. The results demonstrate that opportunistic election calling generates a vote share bonus for the incumbent of as much as 5 percentage points, and is thereby likely to affect electoral accountability.